Eco-friendly composites: developing sustainable solutions for modern engineering - Izadi , Mahboubeh; Bazli , Leila (Journal of Composites and Compounds, 2025)
Eco-Friendly Composites examines the development and application of sustainable composite materials in modern engineering. The primary aim of this initiative is to integrate natural fibers and bio-based polymers to create eco-friendly composites that ensure performance while minimizing their environmental impact. The focus lies in enhancing life cycle assessments, mechanical properties, and processing techniques to guarantee that these materials meet the demands of various industries, including construction, automotive, and aerospace. These composites offer lightweight and cost-effective alternatives to traditional materials, simultaneously reducing carbon footprints by incorporating renewable resources and minimizing waste. While preserving performance and cost-effectiveness, the research underscores that eco-friendly composites hold the potential to transform engineering practices and promote a more sustainable future.